Do Suicide Attempts of Mood Disorder Patients Directly Increase the Risk for a Reattempt? - Aaltonen, Kari I.; Rosenström, Tom; Jylhä, Pekka; Holma, Irina; Holma, Mikael; Pallaskorpi, Sanna; Riihimäki, Kirsi; Suominen, Kirsi; Vuorilehto, Maria; Isometsä, Erkki T. (Frontiers in Psychiatry, 2020)
Background: Preceding suicide attempts strongly predict future suicidal acts. However, whether attempting suicide per se increases the risk remains undetermined. We longitudinally investigated among patients with mood disorders whether after a suicide attempt future attempts occur during milder depressive states, indicating a possible lowered threshold for acting. Methods: We used five-year follow-up data from 581 patients of the Jorvi Bipolar Study, Vantaa Depression Study, and Vantaa Primary Care Depression Study cohorts. Lifetime suicide attempts were investigated at baseline and during the follow-up. At follow-up interviews, life-chart data on the course of the mood disorder were generated and suicide attempts timed. By using individual-level data and multilevel modeling, we investigated at each incident attempt the association between the lifetime ordinal number of the attempt and the major depressive episode (MDE) status (full MDE, partial MDE, or remission). Results: A total of 197 suicide attempts occurred among 90 patients, most during MDEs. When the dependencies between observations and individual liabilities were modeled, no association was found between the number of past suicide attempts at the time of each attempt and subthreshold major depression symptoms. No association between adjusted inter-suicide attempt times and number of past attempts emerged during follow-up. No indication for direct risk-increasing effects was found. Conclusion: Among mood disorder patients, repeated suicide attempts do not tend to occur during milder depressive states than in the preceding attempts. Previous suicide attempts may indicate underlying diathesis, future risk being principally set by the course of the disorder itself.